Managing hydropower dam releases for water users and imperiled fishes with contrasting thermal habitat requirements. Issue 11 (19th August 2019) - Zarri, Liam J.; Danner, Eric M.; Daniels, Miles E.; Palkovacs, Eric P.
Abstract: The construction of dams on large rivers has negative impacts on native species. Environmental flows have been proposed as a tool to mitigate these impacts, but in order for these strategies to be effective they must account for disparate temperature and flow needs of different species. We applied a multi‐objective approach to identify trade‐offs in dam release discharge and temperature for imperiled fishes with contrasting habitat requirements, while simultaneously meeting the needs of human water users. Using the Sacramento River (California, USA) as a case study, our model suggests that current management aimed at providing high discharge for downstream water users and cold water for endangered winter‐run Chinook salmon ( Oncorhynchus tshawytscha ) has detrimental impacts on threatened green sturgeon ( Acipenser medirostris ), which require warm water for juvenile growth. We developed an optimal dam release scenario that can be used to meet the needs of salmon, sturgeon and human water users. Our results show that dam releases can be managed to successfully achieve these multiple objectives in all but the most severe drought years. Synthesis and applications. This study shows that managing dam releases to meet the needs of a single species can have detrimental effects on other native species with different flow and temperature requirements. We applied a multi‐objective approach to balance environmental requirements of multiple species with the needs of human water users. Our findings can be used to guide management of Shasta Dam and our approach can be applied to achieve multi‐object management goals in other impounded rivers. Abstract : Section A represents pre‐dam river conditions, with river flow from left to right, and fish spawning locations along the Sacramento River during their spawning seasons. Section B represents the proposed three‐part strategy to manage resources in Shasta Reservoir for winter‐run Chinook salmon, green sturgeon, and water users. As the season progresses, our proposed management strategy would initially release warm water at low flows when only green sturgeon are present, then decrease temperature to an optimal level when both species are present, and finally decrease temperature further and increase flows for water users when only winter‐run Chinook are present.